Friday Free Lunch, Muslim Middle-Class Piety and Non-Secular Sociality in Yogyakarta Mosque - Faiz, Abd. Aziz (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This paper aims to explain the formation of piety among the urban Muslim middle class, which seeks to achieve a non-secular social life. The practice of providing free lunch on Fridays is widespread among the middle class, especially in residential mosques. This phenomenon appears as a new form of piety that not only shapes religious class formations but also serves as an effort to achieve social class ethics. To achieve this objective, this study relies on qualitative data collected through observations at Bunda Mosque in Yogyakarta, a mosque located in a middle-class residential area. This research finds; First, the Muslim middle class constructs collective piety through rituals, wealth distribution and charity for those performing Friday rituals. The Friday free lunch practice is a direct interpretation of the Sunnah and an act of benefiting others. Second, this practice has an orientation toward achieving a non-secular life, which is not merely about the circulation of economic commodities but also involves the purification of wealth and religio-sociological ethics within the Muslim middle class. This study holds significance for the formation of class-based piety through the redistribution of welfare and offers a religious-sociological ethic that critically challenges the dominance of secular norms in urban space.